Game-based mobile learning with augmented reality: Are teachers ready to adopt it? - Marques, Margarida Morais (2020)
Although only recently mobile augmented reality (AR) games have been adopted for educational purposes, research recognizes their potential and offers guidelines for their use in education, to create smart-learning ecosystems. It is time for teachers to adopt these technologies, but are they receptive to them? The aim of this study is to reveal teachers’ readiness to adopt mobile AR technologies in their practices, after training, bridging the gap between educational practices and research in educational sciences. This paper reports a case study based on a workshop designed to support teachers’ adoption of teaching strategies involving game-based mobile learning (mLearning) with AR. The workshop was conducted under the EduPARK project and offered trainees the opportunity to collaboratively experience the use, in loco, of the EduPARK app for outdoor learning with AR, as well as prompted them to plan educational resources appropriating these technologies. Data were collected through individual questionnaires and focus group interviews, and they were analysed through descriptive statistics, the computing of the educational value scale (EVS) and of the system usability scale (SUS), as well as content analysis. The results show that teachers consider they are ready to integrate mobile AR games in their practices, but they are foreseeing difficulties that need to be addressed. This paper contributes to the field of teacher training in game-based mLearning with AR as it unveils teachers’ readiness to adopt these technologies and why. Moreover, it characterizes a typology of teacher training in this area that, according to the trainee teachers, is successful.